Airway oedema and obstruction in guinea pigs exposed to inhaled endotoxin. Issue 9 (September 1991) - Gordon, T; Balmes, J; Fine, J; Sheppard, D
Abstract : Protein extravasation and airway conductance (SGaw) were examined in awake guinea pigs exposed to inhaled endotoxin or saline for three hours. A significant increase in protein extravasation (as estimated by the leakage of protein bound Evans blue dye) was seen in the conducting airways of endotoxin exposed animals compared with saline exposed animals. Mean dye extravasation was significantly increased by one to threefold in the mainstem and hilar bronchi of endotoxin exposed animals. These changes in extravasation were accompanied by decrements in pulmonary function and by an influx of polymorphonuclear leucocytes into the airway wall. The SGaw decreased significantly by 60-90 minutes into exposure to endotoxin and had decreased by 22% and 34% at the end of exposure in the low and high dose endotoxin groups, respectively. Similar findings were obtained in animals exposed to cotton dust. Contrary to studies suggesting that platelet activating factor (PAF) is involved in the systemic and peripheral lung effects of endotoxin, pretreatment with the PAF antagonist WEB2086 did not prevent the conducting airway injury produced by inhaled endotoxin.